(untitled) (Research, Society and Development, 2022)
This article aims to analyze the perceptions of justice and self-respect that women victims of violence have before and after reporting the violence to the judging authorities, based on the analysis of discussions carried out on the social network Facebook. This is qualitative research. The analysis is based on a historical and conceptual rescue of justice, equity and self-respect, based on John Rawls’ renowned theory of justice, taking into account that violence is increasingly present in women’s daily lives, both in the social sphere and in the homes. The results of this research showed that there is a need for a concern with the efficiency of the measures taken by the justice institutions in cases of violence that occur within the family, since, according to the analysis of the reports in an interaction group on Facebook, most of the time, the protective measure does not have the proper effects on the aggressor, nor does it promote a true feeling of security and integrity in the victims.